Metabolic Effects of Cellular Necrosis Caused by Exfoliative Toxin C (ExhC) from Mammaliicoccus sciuri - Gismene, Carolina [UNESP]; de Moraes, Fábio Rogério [UNESP]; Bauermeister, Anelize; Da Costa, Thyerre Santana; de Freitas Calmon, Marilia [UNESP]; de Almeida Passos Cerbino, Luís Eduardo; Rahal, Paula [UNESP]; Góes, Rejane Maira [UNESP]; de Moraes, Luiz Alberto Beraldo; Tasic, Ljubica; Arni, Raghuvir Krishnaswamy [UNESP] (American Chemical Society (ACS), 2025)
Exfoliative toxins (ETs) are glutamyl endopeptidases (GEPs) belonging to the chymotrypsin-like serine protease family (CLSPs), and they play crucial roles in diverse skin diseases. Specifically, exfoliative toxin C (ExhC), expressed by Mammaliicoccus sciuri, is an atypical CLSP and has been classified as a moonlighting protein due to its ability to induce necrosis in specific cell lines, inhibit the phagocytic activity of macrophages, and cause skin exfoliation in pigs and mice. The latter function is attributed to the high specificity of ExhC for porcine and murine desmoglein-1, a cadherin that contributes to cell-cell adhesion within the epidermis. Although the amino acid residues responsible for ExhC-induced necrosis have been identified, the specific cellular metabolic pathways leading to cell death remain unclear. Herein, we employed nuclear magnetic resonance (NMR) and mass spectrometry (MS) to explore the metabolic pathways affected by the necrotic activity of ExhC in the BHK-21 cell line. The metabolic profile of cells exposed to subtoxic doses of ExhC revealed significant alterations in oxidative stress protection, energy production, and gene expression pathways. The data demonstrate the potential mechanisms of action of ExhC and highlight that this toxin causes cellular damage, even at low concentrations.